From Religious Moderation to Ecotheology: Assessing Institutional Readiness in Indonesian Islamic Universities through a Contextualized Islamic Law Analysis - Ashadi Cahyadi; Adisel Adisel; Ihsan Rahmat; M. Zikri; Hashim Balas (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This study examines the conditions, institutional responses, and readiness of Rumah Moderasi Beragama (Religious Moderation Houses, RMB) in Indonesian Islamic higher education to adopt the ecotheology policy mandated by the Ministry of Religious Affairs for 2025–2029. This constitutes the first empirical study establishing a nexus between ecotheological policy and organizational readiness. Using a qualitative doctrinal-empirical approach, data were collected from seven RMBs and the Ministry’s Religious Moderation Working Group through observation, in-depth interviews, and document analysis. Findings reveal that institutional responses remain predominantly symbolic or ambiguous, lacking operational plans, structural support, and resource allocation. The mean readiness score was below 46% of ideal capacity, with heatmap analysis exposing deficiencies in competence, collective efficacy, and funding. Applying a contextualized Islamic law framework — integrating fiqh al-bi’ah, fiqh moderat, ushul fiqh, and qawāʿid fiqhiyyah — this study finds that the observed institutional decoupling constitutes simultaneously an organizational failure and a normative gap in Islamic environmental jurisprudence. This study recommends policy interventions through ecotheology unit establishment, capacity building, resource mobilization, and cross-sector collaboration. This study makes three original contributions. First, it provides the first empirical mapping of RMB institutional readiness for ecotheology adoption, filling a gap at the intersection of Islamic higher education governance and environmental religious policy. Second, it introduces a multi-dimensional readiness heatmap instrument grounded in organizational change theory, offering a replicable diagnostic tool for Islamic institutional policy research. Third, it advances a contextualized Islamic law framework — integrating fiqh al-bi’ah, fiqh moderat (wasathiyyah), ushul fiqh, and qawāʿid fiqhiyyah — as an analytical lens for evaluating ecotheology policy adoption in Indonesian Islamic institutions, bridging the gap between Islamic jurisprudential norms and institutional governance realities.